STRUCTURE AND CONTENT OF SPECIALIZED MAPS AND REGISTERS: STRUCTURE AND CONTENT OF SPECIALIZED MAPS AND REGISTERS - Niyazi-Yusuf, Mirem E. (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
The article examines the content and main components of specialized maps and registers as part of the cadastre system in the Republic of Bulgaria. It presents their key structural elements, thematic content, and the interrelation between maps and registers. Emphasis is placed on their role in territorial management, spatial planning, and the maintenance of up-to-date spatial information.